Polarization dependent multiphoton absorption in ZnO thin films - Hollinger, Richard; Gupta, Dishiti; Zapfl, Maximilian; Karst, Maximilian; Roeder, Robert; Uschmann, Ingo; Reisloehner, Udo; Kartashov, Daniil; Ronning, Carsten; Spielmann, Christian (Journal of Physics D: Applied Physics, 2020)
We present a simple non-destructive approach for studying the polarization dependence of nonlinear absorption processes in semiconductors. The method is based on measuring the yield of the near UV photoluminescence as a function of polarization and intensity of femtosecond laser pulses. In particular, we investigated the polarization dependence of three photon laser absorption in intrinsic and Al-doped ZnO thin films. Both specimen show stronger emission for linearly polarized excitation compared to circular polarization. The ratios for the three-photon absorption coefficients are about 1.8 and independent of the doping. It is shown that Al-doped films have lower threshold for stimulated emission in comparison to the intrinsic films.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Multiphoton absorption; Polarization; Stimulated emission; Zno thin film